2019
DOI: 10.4103/ijmr.ijmr_1405_17
|View full text |Cite
|
Sign up to set email alerts
|

What makes non-cirrhotic portal hypertension a common disease in India? Analysis for environmental factors

Abstract: In India, an unexplained enteropathy is present in a majority of non-cirrhotic intrahepatic portal hypertension (NCIPH) patients. Small intestinal bacterial contamination and tropical enteropathy could trigger inflammatory stimuli and activate the endothelium in the portal venous system. Groundwater contaminated with arsenic is an environmental factor of epidemic proportions in large areas of India which has similar consequences. Von Willebrand factor (a sticky protein) expressed by activated endothelium may p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…OPV is poorly understood since it lacks pathognomonic clinical features. It is a subtype of noncirrhotic portal hypertension (NCPH) which itself is rare in the USA but is relatively common in India [ 4 ]. The etiopathogenesis of OPV is unknown and several hypotheses are proposed including antiretroviral therapy, hypercoagulability, genetic predisposition, recurrent bacterial infections, and chemical/toxin exposure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…OPV is poorly understood since it lacks pathognomonic clinical features. It is a subtype of noncirrhotic portal hypertension (NCPH) which itself is rare in the USA but is relatively common in India [ 4 ]. The etiopathogenesis of OPV is unknown and several hypotheses are proposed including antiretroviral therapy, hypercoagulability, genetic predisposition, recurrent bacterial infections, and chemical/toxin exposure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] A main consequence of chronic high-level arsenic exposure is NCIPH that is a result of chronic microangiopathy of portal vein branches, leading to intrahepatic portal vein occlusion. 38 In agreement with this, populations with elevated ingest of arsenic in drinking water have a high prevalence of NCIPH in presence of skin arsenicosis. 32,33,35,39 In fact, a study performed in Chandigarh, India, showed that arsenic levels in liver biopsy of patients of NCIPH were significantly higher (0.887 ± 0.404 ppm) compared with cirrhosis patients (0.178 ± 0.171 ppm) and control individuals (0.071 ± 0.058 ppm); interestingly, some of the NCIPH patients consumed drinking water with high arsenic content (0.360 and 0.549 ppm).…”
Section: Epidemiologymentioning
confidence: 59%
“…5 There are various disorders associated with noncirrhotic portal hypertension including chronic or recurrent infections, genetic disorders, thrombophilia, immunological disorders, and exposure to drugs or toxins. 1,2,9 These factors are believed to contribute to portal vascular endothelium aggregation; however, the precise pathophysiology is likely multifactorial and remains unknown. 2 Our patient had no recent or history of infections, bleeding issues, or genetic/immunological disorders.…”
Section: Discussionmentioning
confidence: 99%